2003
DOI: 10.1002/macp.200350036
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Mechanistic Studies of Carboxylic Acid–Bisoxazoline Chain‐Coupling Reactions

Abstract: Kinetic studies of the reactions between a model carboxylic acid and bisoxazoline coupling agents, namely 2,2′‐(1,3‐phenylene)bis(2‐oxazoline) (mbox), 2,2′‐(1,4‐phenylene)bis(2‐oxazoline) (pbox), and 2,2′‐(2,6‐pyridylene)bis(2‐oxazoline) (pybox), were carried out in bulk at 140–220 °C. A second‐order two‐step reaction mechanism was proposed and was verified by the experimental results. The results also indicate that the reactivity of the oxazoline groups is unchanged after the reaction of the other oxazoline g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 33 publications
(55 reference statements)
1
43
0
Order By: Relevance
“…Figure 4 for the case of the reaction of PA12-1 with the three bisoxazolines. At the beginning of reaction, the experimental data perfectly fit the theoretical curves obtained using the rate constant values determined for the model reactions carried out on dodecanoic acid at 200 8C [13] (mbox:…”
Section: Reactions Between Carboxy-terminated Polyamide-12 (Pa12) Andmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 4 for the case of the reaction of PA12-1 with the three bisoxazolines. At the beginning of reaction, the experimental data perfectly fit the theoretical curves obtained using the rate constant values determined for the model reactions carried out on dodecanoic acid at 200 8C [13] (mbox:…”
Section: Reactions Between Carboxy-terminated Polyamide-12 (Pa12) Andmentioning
confidence: 99%
“…In a previous study, we have shown using model compounds that the carboxylic acid-oxazoline reactions are second order and that oxazoline groups are equireactive, i.e., oxazoline group reactivity does not change after other oxazoline groups of the same molecule has reacted. [13] Therefore, in the case of a stoichiometric reaction, the variations of carboxylic acid concentration, [COOH], versus time t should follow Equation (1),…”
Section: Reactions Between Carboxy-terminated Polyamide-12 (Pa12) Andmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, numerous examples are given that describe the utilization of reactive bifunctional compounds as chain extenders and coupling agents, such as diisocyanates, [1][2][3] bisoxazolines, [4][5][6][7][8][9][10] bisepoxides, [11][12][13][14] bislactamates, [15][16][17] and bisoxazolones. [18,19] In the case of polymers that contain different reactive groups, a combination of coupling agents has been applied.…”
Section: Feature Articlementioning
confidence: 99%